iCare: Personal Health Assistant Using Microsoft Azure Cloud - Krishnaveni, S.; Jothi, B.; Jeyasutha, J.; Sivamohan, S. (Indian Journal of Computer Science, 2016)
Nowadays healthcare becomes a critical problem due to lack of availability of expert doctors.In order to overcome this problem we are proposing a personal health Assistant system which will be unified with cloud computing. This paper proposes the iCare Personal Health Assistant from a technical perspective and its benefits for users. iCare personal health assistant monitors patient'shealth in a very appropriate manner and produces a warning when the patient's vital parameters exceeds the normal value. The histological patient data is transferred to the Azure cloud storage that can be accessed by expert doctors and patients via iOS mobile app. iOS 8 App which can read various health data parameters provided by iOS Health Kit Framework and an Azure Web application which collectively stores all the data to perform simple analytics and report on health conditions for a specific time. The Azure Web application will be developed using ASP.NET and hosted in Microsoft Azure Cloud. Azure Web services and Azure Mobile Services are used to send push notifications. Thus, users get the latest health report along with few suggestive actions to remedy that health condition, if any, and this allows users to adjust their nutrition and activities accordingly.